The social contract & discourses - Rousseau, Jean-Jacques, 1712-1778; Cole, G. D. H. (George Douglas Howard), 1889-1959 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Social Contract & Discourses" by Jean-Jacques Rousseau is a foundational work of political philosophy written in the late 18th century. The text explores the relationship between individuals and the state, examining how legitimate political authority can be established and justified. Central to Rousseau's argument is the idea of the social contract, which posits that individuals collectively agree to form a society that is governed by the general will aimed at the common good. At the start of the work, Rousseau provocatively states, (3z(BMan is born free; and everywhere he is in chains,(3y (Bindicating his exploration of how social and political structures often oppress human freedom. He questions the legitimacy of authority derived from force and differentiates between natural and societal bonds, suggesting that while the family represents the first natural society, political institutions must be based on mutual consent and conventions. By delving into these themes, Rousseau sets the stage for a deeper inquiry into the nature of freedom, the role of government, and the principles that underpin legitimate social orders. (This is an automatically generated summary.)s
Release date is 2014-07-19
E-text prepared by Marc D'Hooghe (http://www.freeliterature.org) from page images generously made available by the Google Books Library Project (http://books.google.com)
Keywords: Economics; Political science -- Early works to 1800; Social contract